2018
DOI: 10.1002/jlb.5a0817-328rrr
|View full text |Cite
|
Sign up to set email alerts
|

Cenicriviroc inhibits trans-endothelial passage of monocytes and is associated with impaired E-selectin expression

Abstract: Incidences of cardiovascular diseases (CVD) are high among virologically suppressed HIV-infected individuals. Monocyte activation and trafficking are key mechanisms in the evolution of CVD. We studied the ability of cenicriviroc (CVC), a dual C-C chemokine receptor type 2 (CCR2) and CCR5 antagonist, to influence the migration of monocytes from HIV-infected individuals on antiretroviral therapy (ART). Monocytes were derived from 23 ART-suppressed HIV-infected and 16 HIV-uninfected donors. In a trans-endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In comparison to maraviroc, cenicriviroc possesses higher efficiency in disruption of links between cells. 171 Nowadays, cenicriviroc-related clinical trials have demonstrated that the drug has both antiviral and anti-fibrosis effects in the condition of infections, non-alcoholic steatohepatitis (NASH), primary sclerosing cholangitis (PSC) (NCT02653625) and many other conditions. 172 , 173 …”
Section: Treatment Targeting Ccl5/ccr5mentioning
confidence: 99%
“…In comparison to maraviroc, cenicriviroc possesses higher efficiency in disruption of links between cells. 171 Nowadays, cenicriviroc-related clinical trials have demonstrated that the drug has both antiviral and anti-fibrosis effects in the condition of infections, non-alcoholic steatohepatitis (NASH), primary sclerosing cholangitis (PSC) (NCT02653625) and many other conditions. 172 , 173 …”
Section: Treatment Targeting Ccl5/ccr5mentioning
confidence: 99%
“…Dysregulation of the immune system due to HIV itself, coinfections, or bystander mediators of inflammation may drive inappropriate activation and retention of immune cells within tissue sites such as blood vessels, liver, adipose tissues, and the central nervous system (CNS). Circulating immune cell populations that include activated monocytes expressing pro-coagulants (eg, tissue factor), as well as increased numbers of mature activated CD8 + T cells that can home to endothelial surfaces via expression of homing receptors including the fractalkine receptor (CX3CR1), lymphocyte function-associated antigen 1 (LFA-1), macrophage-1 antigen (Mac-1) [19,20], C-C chemokine receptor type 2 (CCR2), and type 5 (CCR5) [21], are detected in PWH, and may be linked to development of CVD and other comorbidities [22][23][24][25][26]. Altered migration of activated immune cells to, and retention within, these tissues may also influence development of other end-organ diseases.…”
Section: Immune Cell Populations and Traffickingmentioning
confidence: 99%
“…At least some of the molecules that attract macrophages to the site of virally damaged cells have been identified [35]. The I-SPY-Covid-19 Trial is investigating the clinical utility of Cenicriviroc against macrophage attractant molecules CCR-2 and CCR-5 [36]. Preventing macrophages from gathering in alveoli would likely be most effective in the several days before SF levels rise.…”
Section: Discussionmentioning
confidence: 99%